2023
DOI: 10.1109/taes.2023.3244773
|View full text |Cite
|
Sign up to set email alerts
|

Formation-of-Arrays Antenna Technology for High-Throughput Mobile Non-Terrestrial Networks

Abstract: Effective integration of terrestrial and nonterrestrial segments is one of the key research avenues in the design of current and future wireless communication networks. To this aim, modern communication-satellite constellations intend to attain sufficiently high throughput in terms of bit rate per unit area on the ground by rather aggressive patterns of spatial frequency reuse. This goal calls for on-board narrow-beam antennas, whose size turns out to be in many cases incompatible with the size/mass and accomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Nevertheless, swarms of small satellites for D2C connectivity have received limited attention. The paper in [5] presented a formation of sub-arrays in geostationary Earth orbit (GEO) and LEO scenarios, but the LEO performance derived is similar to the conventional approach. The paper in [6] considered a swarm creating a distributed phased array for D2C connectivity, emphasizing the importance of swarm geometry in antenna performance, but considering only one radiating element per small satellite.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, swarms of small satellites for D2C connectivity have received limited attention. The paper in [5] presented a formation of sub-arrays in geostationary Earth orbit (GEO) and LEO scenarios, but the LEO performance derived is similar to the conventional approach. The paper in [6] considered a swarm creating a distributed phased array for D2C connectivity, emphasizing the importance of swarm geometry in antenna performance, but considering only one radiating element per small satellite.…”
Section: Introductionmentioning
confidence: 99%
“…As is known, the effort of integrating a nonterrestrial segment into current 5G (terrestrial) networks and forthcoming 6G networks is formidable [1]. An analysis performed in [2] concluded that a real integration of the two segments, in particular allowing end-users to utilize a smartphone, calls for the adoption of radically new technologies, such as the distributed very-large antenna 0018-9251 © IEEE for low Earth orbit (LEO) and geostationary Earth orbit (GEO) satellites introduced in [3]: a formation of arrays (FoA). The satellite systems currently deployed to provide direct to hand-held communications (e.g.…”
mentioning
confidence: 99%
“…Our 4G service target is justified by the fact that providing 4G-like data rates to a conventional terrestrial hand-held terminal already represents a big technological challenge for the space segment, in particular for a GEO orbit. In terms of our current performance targets, the reader can refer to [3], whereby we size the space segment to provide data rates in the order of Mbps to a conventional low-antenna gain hand-held UT having the characteristic specified by 3GPP 5G NTN documents (e.g. [6]).…”
mentioning
confidence: 99%
See 2 more Smart Citations